Library Client Service Record (LibCSR) tool design and prototype of an integrated user database for the UP Diliman University Library General Reference Section - Lopez, Edfe Angelo A. (2015)
Library Client Service Record (LibCSR) is a system where a reference librarian can view library user's information and their reference transaction histories. The researcher made a prototype of LibCSR through systems analysis and design following the principles of user-centered systems design (USCD). Through purposive sampling, the researcher chose nine librarians from the U.P. Diliman University Library General Reference Section to perform a user evaluation and system usability evaluation for the prototype of LibCSR. A Likert scale type of questionnaire was given to the librarians to rate the prototype of LibCSR. An open-ended statement asking for the librarian's comments and suggestions about the prototype was also incorporated on the questionnaire. The demonstration of the LibCSR prototype was shown one by one to the librarians, followed by the one to one hands-on experience on using the prototype before answering the questionnaire. LibCSR was also compared to two popular reference service systems, namely QuestionPoint and RefTracker. Many papers of studies and reviews about QuestionPoint and RefTracker were carefully chosen. Expert's opinions through personal communications were also added as part of the review. The listed features of both QuestionPoint and RefTracker in their respective websites were also used for the comparison.